2009
DOI: 10.1155/2009/384683
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regulation of Contraction-Induced Akt/mTOR/p70S6k Pathway Signaling in Skeletal Muscle of the Obese Zucker Rat

Abstract: Increased muscle loading results in the phosphorylation of the 70 kDa ribosomal S6 kinase (p70S6k), and this event is strongly correlated with the degree of muscle adaptation following resistance exercise. Whether insulin resistance or the comorbidities associated with this disorder may affect the ability of skeletal muscle to activate p70S6k signaling following an exercise stimulus remains unclear. Here, we compare the contraction-induced activation of p70S6k signaling in the plantaris muscles of lean and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…1). For example, Katta et al (2009a,b) showed that Akt serine and threonine phosphorylation is increased in lean but not insulin resistant obese Zucker rats following a bout of eccentric exercise. This defect of Akt activation in the obese Zucker is associated with diminished activation of the Akt downstream mTOR and p70S6k (Katta et al, 2009a,b), a signaling cascade critical for protein synthesis and exercise‐induced muscle hypertrophy.…”
Section: Roles Of Akt In Muscle Contractionmentioning
confidence: 99%
“…1). For example, Katta et al (2009a,b) showed that Akt serine and threonine phosphorylation is increased in lean but not insulin resistant obese Zucker rats following a bout of eccentric exercise. This defect of Akt activation in the obese Zucker is associated with diminished activation of the Akt downstream mTOR and p70S6k (Katta et al, 2009a,b), a signaling cascade critical for protein synthesis and exercise‐induced muscle hypertrophy.…”
Section: Roles Of Akt In Muscle Contractionmentioning
confidence: 99%
“…Additionally, although activity of mTORC1‐targeting substrates is reduced in T2DM under insulin exposure, the response of muscle hypertrophy to RT did not differ between T2DM and healthy rats. Previously, it was observed that although fed‐state mTORC1 activity is reduced due to T2DM, the response of mTORC1 activation by high‐force muscle contraction does not necessarily diminish (Katta et al., , ). Furthermore, a previous study showed that streptozotocin‐induced pharmacological lack of insulin secretion caused muscle atrophy, but did not impair muscle hypertrophy to overload in murine skeletal muscle (Fortes et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These adaptations were related to both the muscle protein synthesis response via the activation of mTORC1 (Ogasawara et al., ; West et al., ) and myonuclear accretion via the satellite cells (Egner, Bruusgaard, & Gundersen, ; Fry et al., ; McCarthy et al., ; Snijders et al., ). Interestingly, previous rodent and human experiments showed that, unlike a nutritional stimulus, mTORC1 activation and the MPS response to acute resistance exercise or high‐force muscle contraction were not impaired in T2DM (Hulston et al., ; Katta et al., ). Furthermore, a previous animal study observed that satellite cell activation to muscle contraction is not impaired in the T2DM model rat (Peterson et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This multi-protein eIF4F complex functions to assist in the binding of mRNA towards the 40S ribosomal subunit [8,9] , and subsequently initiation protein translation and MPS [11][12][13][14] . The mTOR pathway also activates p70S6K, which then phosphorylates its effector ribosomal protein S6 (rpS6) that can assist in the enhancement of protein translation from template mRNA [5,8,10,15] . The activation of p70S6K, and the subsequent phosphorylation of rpS6, can induce enhanced translation of mR-NAs containing the 5' terminal oligopyrimidine tract (5'-TOP) (encoding elongation factors as well as ribosomal proteins.…”
mentioning
confidence: 99%